α-GLUCOSIDASE INHIBITORY ACTIVITY AND FORMULATION OF SOLID LIPID NANOPARTICLE CONTAINING ETHANOL 70% STANDARDIZED EXTRACT OF KUMIS KUCING LEAVES (Orthosiphon stamineus Benth.) - Risma Marisi Tambunan; Winda Dwi Juliyanti (Fakultas Farmasi Universitas Pancasila, 2018)
Kumis kucing leaves (Orthosiphon stamineus Benth.) are one type of plants that is able to inhibit the activity of α-glucosidase enzyme. This study aims to formulate Solid Lipid Nanoparticle from ethanol 70% standardized extract of kumis kucing leaves and which give α-glucosidase enzyme inhibitory activity. The result of SLN characteristic for particle size of formula I, II and III shows the result of 51,60 nm; 12.81 nm; 11.87 nm and zeta potential of formula I, II and III show the results -27.67; -10,7; -15.0, respectively. The results of the α-glucosidase enzyme inhibitory activity of the standardized extract, SLN formula I, II and III respectively showed IC50 of 132.9 ppm; 130.3 ppm; 131.4 ppm; 132.2 ppm and Acarbose as comparison showed IC50 of 50.0 ppm. Data processing using t-test statistically at α = 0,05 showed that extract and SLN of formula I had significant difference, thus the best SLN formula was formula I with concentration of tween 80 and propylenglycol of 6% and 10%.